Laying the fishing nets for a catch - Mumbai Archive Project Team (Jio Institute, 2024)
The ebb and flow of tides, along with the changing seasons when certain types of fish are available, dictate the catch. Most fishermen use vertical nets, called gill nets, that trap fish by their gills. After laying the nets, the boats wait for four to five hours before hauling them back on board.